Cyclohexanohemicucurbit[8]uril Inclusion Complexes With Heterocycles and Selective Extraction of Sulfur Compounds From Water - Shalima, Tatsiana; Mishra, Kamini A.; Kaabel, Sandra; Ustrnul, Lukas; Bartkova, Simona; Tõnsuaadu, Kaia; Heinmaa, Ivo; Aav, Riina (Frontiers in Chemistry, 2021)
Solid phase extraction, that utilizes selective macrocyclic receptors can serve as a useful tool to develop removal of chemical wastes. Hemicucurbiturils are known to form inclusion complexes with suitably sized anions, however, their use for selective binding of non-charged species is still very limited. In this study, we found that cyclohexanohemicucurbit[8]uril encapsulates five- and six-membered sulfur- and oxygen-containing unsubstituted heterocycles, which is investigated by single crystal X-ray diffraction, NMR spectroscopy, isothermal titration calorimetry and thermogravimetry. The macrocycle acts as a promising selective sorption material for the extraction of sulfur-heterocycles, such as 1,3-dithiolane and α lipoic acid, from water.